Epidemiology of prediabetes and diabetes in Namibia, Africa: A multilevel analysis - Adekanmbi, Victor T. (J Diabetes, 2018)
BACKGROUND: Diabetes is a leading cause of progressive morbidity and early mortality worldwide. Little is known about the burden of diabetes and prediabetes in Namibia, a Sub‐Saharan African (SSA) country that is undergoing a demographic transition. METHODS: We estimated the prevalence and correlates of diabetes (defined as fasting [capillary] blood glucose [FBG] ≥126 mg/dL) and prediabetes (defined by World Health Organization [WHO] and American Diabetes Association [ADA] criteria as FBG 110–125 and 100–125 mg/dL, respectively) in a random sample of 3278 participants aged 35–64 years from the 2013 Namibia Demographic and Health Survey. RESULTS: The prevalence of diabetes was 5.1% (95% confidence interval [CI]: 4.2–6.2), with no evidence of gender differences (P = 0.45). The prevalence of prediabetes was 6.8% (95% CI 5.8–8.0) using WHO criteria and 20.1% (95% CI 18.4–21.9) using ADA criteria. Male sex, older age, higher body mass index (BMI), and occupation independently increased the odds of diabetes in Namibia, whereas higher BMI was associated with a higher odds of prediabetes, and residing in a household categorized as “middle wealth index” was associated with a lower odds of prediabetes (adjusted odds ratio 0.71; 95% credible interval 0.46–0.99). There was significant clustering of prediabetes and diabetes at the community level. CONCLUSIONS: One in five adult Namibians has prediabetes based on ADA criteria. Resources should be invested at the community level to promote efforts to prevent the progression of this disease and its complications.